Stratification of Health Professional Education and Its Funding Disparities: Evidence From China During the Period of 1998-2017 - Wenjuan Gao; Wenzhuo Li; Yue Zang; Yue Zang; Yuxin Zhong; Yuxin Zhong; Hongbin Wu; Hongbin Wu (Frontiers Media S.A., 2022)
Background: The finance of health professional education (HPE) is of immense importance for effective and sustainable health systems, yet relevant empirical research was scarce due to the lack of financial data. The study aimed to bridge the gap by presenting the scenario of finance for health professional institutions (HPIs) of different tiers in China and exploring how the stratification of institutions affected their funding disparities.Methods: The study employed data collected from the Ministry of Education in China, and selected the HPIs mainly based on the World Directory of Medical Schools. The funding levels and disparities of China's HPIs during the period (1998-2017) were analyzed with descriptive statistics, and the indicators of funding per institution and funding per student were both considered. The average funding in HPIs was presented by tiers, and the Gini coefficient and Theil index were employed to describe the differences in financing among HPIs over the span.Results: The study found that the number of HPIs has kept growing over the past two decades, with both the funding per institution and the funding per student increasing steadily. Specifically, the average funding per institution of the three tiers increased by 31.5 times, 13.4 times, and 10.5 times separately, with the first-tier universities having an absolute advantage compared to lower tiers. As for the financing disparities among HPIs, the Gini coefficient of the funding per institution maintained to be over 0.5, with the third-tier institutions scoring the highest, while the Gini coefficient of the funding per student all ranged approximately from 0.2 to 0.3. Through the decomposition of the inequalities measured by the Theil index, the share of the between-tier difference in per-institution funding grew from 29.7 in 1998 to 77.9% in 2017.Conclusions: The funding disparities between tiers of HPIs in China gradually became more accentuated, with the top-tier institutions taking up the largest share. Although the stratified development in HPE has posed a challenge to the unified quality assurance of medical personnel training, it may also be regarded as an effective pathway for developing countries like China to achieve stable development in health professional education.